Multimorbidity: Not Just for the West - Amitava Banerjee; John Hurst; Edward Fottrell; J. Jaime Miranda (Ubiquity Press, 2020)
"A multimorbidity lens creates exciting opportunities to reconceptualise health and wellbeing in all its complexity. We need to improve health metrics to capture this complexity and strengthen health services to respond to it."